MODEL PELATIHAN TERPADU UNTUK MENINGKATKAN FUNGSI DAN PERAN SOSIAL ANAK DALAM MEMBINA KEMANDIRIAN - Akmala Hadita (JIV-Jurnal Ilmiah Visi, 2011)
Some problems are often faced in educating children to be self-reliant. On the other hand independency is much required in their future life. This research conducted in RSPA Cisurupan, Garut, in April 2010 until April 2011, aimed at developing an integrated training model to improve function and social roles of the children in the independency. Employing research and development design with planning, preparation, implementation and maintaining, as well as evaluation, the model development involved the parents or the family members and the children. The research produced the Integrated Training Model to Improve the Function and Social Roles of the Children in Developing the Self-reliance, which had been validated in this research.